How do soil micro‐organisms respond to N, P and NP additions? Application of the ecological framework of (co‐)limitation by multiple resources. (24th May 2019) - Ma, Beibei; Zhou, Xiaolong; Zhang, Qi; Qin, Mingsen; Hu, Linggang; Yang, Kena; Xie, Zhen; Ma, Wenbin; Chen, Beibei; Feng, Huyuan; Liu, Yongjun; Du, Guozhen; et al.
Abstract: Nitrogen (N) and phosphorus (P) often limit biological processes in terrestrial ecosystems. Based on previous studies mainly focusing on plants, the concept of resource limitation has evolved towards a theory of (co)limitations by multiple resources. However, this ecological framework has not been applied to analyse how soil micro‐organisms and plants concurrently respond to N and/or P addition, and whether these responses are constrained by phylogenetic relatedness. Here, we applied this framework to analyse microbial and plant responses at community and taxon levels to different fertilization treatments (four N levels without P; four P levels without N and four NP levels) in Tibetan grasslands. Total plant biomass showed serial limitation by N then P, and most plant species were limited by N only. Total archaeal abundance decreased with P addition, but diverse nutrient limitation types were observed for archaeal taxa. Closely related archaeal taxa tended to similarly respond to N, and functional similarity between distant archaeal groups was observed for response to P, possibly due to functional convergence. In contrast, total bacteria slightly increased with P addition only when plants remained N limited, whereas without N limitation, plants rather than bacteria benefited from P addition. Most bacterial taxa were limited by other resources than N and P, and no clear phylogenetic signals were observed regarding bacterial responses to N/P additions. Synthesis. We propose a novel approach for characterizing microbial response types to nutrient addition. It demonstrates that in Tibetan meadows, most dominant plant species, archaea and bacteria, respectively, depend on N, both N and P and other resources. Abstract : We propose a novel approach for characterizing microbial response types to nutrient addition. It demonstrates that in Tibetan meadows, most dominant plant species, archaea and bacteria, respectively, depend on N, both N and P and other resources. 摘要: 氮 (N) 和 (P) 是陆地生态系统中限制生物过程的关键元素, 在以往以植物为主体的研究基础上，资源限制的概念已经发展成为多资源共同限制的理论. 然而, 这一生态学理论尚未用于分析土壤微生物和植物如何同时对N和/或P添加响应, 以及这些响应是否受到系统发育相关性的限制. 本研究应用该理论模型分析了青藏高原高寒草甸不同施肥处理 (4N水平不施P; 4P水平不施N; 4NP水平）在群落及类群水平上的微生物和植物响应关系. 植物总生物量显示先N后P限制，多数植物仅受N限制。古菌丰度随P添加量的增加而降低，但对古菌类群的营养限制类型有所不同. 进化关系较近的古菌类群对氮的反应趋向相似, 进化关系较远的古菌类群对磷的反应趋向于功能趋同. 相反, 当植物保持N限制性时, 细菌群落丰度随着P的加入而略有增加, 而植物则胜过细菌, 使其受益于没有N限制的P添加. 除N、P外, 大多数细菌类群受到其他资源的限制, 且在细菌类群响应N/P添加中未检测到显著的系统发育信号. 综上, 本研究首次对微生物响应营养元素添加的类型进行定义. 结果表明, 在青藏高原高寒草甸生境中, 大多数优势植物种类、古菌和细菌的营养限制类型分别是N限制、N和P限制以及其他营养元素限制.